Propuesta de Mejoramiento del Sistema de Identificación, Evaluación, y Control de Riesgos para el Área Productiva Conservas en Almíbar de la empresa “La Conchita”. - Neto Chusín, José Luis (2011)
This investigation work that we have here was done in the Productive Area of Preserves in Syrup of the Company of Preserves and Vegetables "The Shell." The general aim of the investigation is: To elaborate a proposal of improvement of the System for the Identification, Evaluation, and Control of Risks of the Area of Preserves in Syrup of the company of Preserves and Vegetables "The Shell." Also in the investigation we have the following specific objectives: To analyze the Cuban norms "NC: 18001" and the effective resolutions at the present time inside of the Security and Health field of the Work. To identify and evaluate the current conditions of risk for each one of the work positions in the productive area of Preserves in Syrup. To propose a plan of improvement, to reduce the accidents and professional illnesses that they were found in the study area.